2017
DOI: 10.1063/1.4977789
|View full text |Cite
|
Sign up to set email alerts
|

Direct observation of dramatically enhanced hole formation in a perovskite-solar-cell material spiro-OMeTAD by Li-TFSI doping

Abstract: Electron spin resonance (ESR) spectroscopy of 2,2′,7,7′-tetrakis-(N,N-di-p-methoxyphenylamine)9,9′-spirobifluorene (spiro-OMeTAD) thin films and perovskite (CH3NH3PbI3)/spiro-OMeTAD layered films are reported. Clear ESR signals (g = 2.0030) were observed by adding a dopant lithium bis(trifluoromethanesulfonyl)imide (Li-TFSI) to the spiro-OMeTAD thin films, which directly showed the spin (hole) formation in spiro-OMeTAD by the Li-TFSI doping. The number of spins in the spiro-OMeTAD thin film has increased by mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 29 publications
(46 reference statements)
3
54
1
Order By: Relevance
“…There are several factors that contributed to the observed performance improvement. One factor is the photo‐doping effect . Light soaking of perovskite and TiO x were also suggested as factors contributing to performance improvements after short light exposure .…”
Section: Resultsmentioning
confidence: 99%
“…There are several factors that contributed to the observed performance improvement. One factor is the photo‐doping effect . Light soaking of perovskite and TiO x were also suggested as factors contributing to performance improvements after short light exposure .…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3][4][5] Moreover they have a better thermal and chemical stability in comparison with pyridinium and imidazolium-based ILs. [10][11][12] It can be found in two different conformational geometries: the transoid one with a C2 symmetry is more stable than the cisoid one, which has a C1 symmetry. TFSI is a well known anion, with large applications in electrochemistry, where it has found use, for instance, as component of several types of battery electrolytes [7][8][9] or as additive in dye-sensitized solar cells.…”
Section: Introductionmentioning
confidence: 99%
“…TFSI is a well known anion, with large applications in electrochemistry, where it has found use, for instance, as component of several types of battery electrolytes [7][8][9] or as additive in dye-sensitized solar cells. [10][11][12] It can be found in two different conformational geometries: the transoid one with a C2 symmetry is more stable than the cisoid one, which has a C1 symmetry. [13] However, from the calculations the energy difference between these two conformers is as low as 2.2 kJ/mol, and therefore in the liquid state both of them are usually present.…”
Section: Introductionmentioning
confidence: 99%
“…In the recent past, ESR spectroscopy has been successfully employed to better understand the performance of polymer solar cell materials [9]. To date, there has been very limited work reported that investigate the point defects that arise during the fabrication process of perovskite solar cells using the ESR technique [10,11]. For instance, Shkrobe et al studied [10] the charge trapping process in bulk polycrystals of photovoltaically active perovskites and related halogenoplumbate compounds using ESR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the holes are trapped by organic cations whereas Pb 2+ centres trap electrons. In a more recent work [11], Namatame and co-authors employed room-temperature ESR spectroscopy to observe dramatic enhancement of hole formation in a perovskite solar cell material spiro-OMeTAD by Li-TFSI doping. In addition, they observed photo generated spins upon in-situ light irradiation.…”
Section: Introductionmentioning
confidence: 99%